Document Sample

RECURSIVE ALGORITHMS Recurrence Relation • An equation that defines each element of a sequence in terms of one or more earlier elements • Example: – Fibonacci Numbers may be described by the recurrence relation: • F(n) = F(n-1) + F(n-2) – where F(1)=1 – and F(2)=1 Solving Recurrence Relations • Many techniques exist to solve specific types of recurrence relations • None have proven to provide a solution to all recurrence relations Backward Substitution • Linear Search – Recursively look at an element (constant work, c), then search the remaining elements… • T(n) = T( n-1 ) + c • “The cost of searching n elements is the cost of looking at 1 element, plus the cost of searching n-1 elements” Linear Search • We’ll “unwind” a few of these T(n) = T(n-1) + c (1) But, T(n-1) = T(n-2) + c, from above Substituting back in: T(n) = T(n-2) + c + c Gathering like terms T(n) = T(n-2) + 2c (2) Linear Search • Keep going: T(n) = T(n-2) + 2c T(n-2) = T(n-3) + c T(n) = T(n-3) + c + 2c T(n) = T(n-3) + 3c (3) T(n) = T(n-4) + 4c (4) List of intermediates Result at ith unwinding i T(n) = T(n-1) + 1c 1 T(n) = T(n-2) + 2c 2 T(n) = T(n-3) + 3c 3 T(n) = T(n-4) + 4c 4 Linear Search • An expression for the kth unwinding: T(n) = T(n-k) + kc • We have 2 variables, k and n, but we have a relation • T(d) is constant (can be determined) for some constant d (we know the algorithm) • Choose any convenient number to stop. Linear Search • Let’s decide to stop at T(0). – When the list to search is empty, you’re done… • 0 is convenient, in this example… Let n-k = 0 => n=k • Now, substitute n in everywhere for k: T(n) = T(n-n) + nc T(n) = T(0) + nc = nc + c0 = O(n) ( T(0) is some constant, c0 ) Binary Search • Algorithm – “check middle, then search lower ½ or upper ½” • T(n) = T(n/2) + c where c is some constant, the cost of checking the middle… Binary Search Let’s do some quick substitutions: T(n) = T(n/2) + c (1) but T(n/2) = T(n/4) + c, so T(n) = T(n/4) + c + c T(n) = T(n/4) + 2c (2) T(n/4) = T(n/8) + c T(n) = T(n/8) + c + 2c T(n) = T(n/8) + 3c (3) Binary Search Result at ith unwinding i T(n) = T(n/2) + c 1 T(n) = T(n/4) + 2c 2 T(n) = T(n/8) + 3c 3 T(n) = T(n/16) + 4c 4 Binary Search Result at ith unwinding i T(n) = T(n/2) + c =T(n/21) + 1c 1 T(n) = T(n/4) + 2c =T(n/22) + 2c 2 T(n) = T(n/8) + 3c =T(n/23) + 3c 3 T(n) = T(n/16) + 4c =T(n/24) + 4c 4 Binary Search • After k unwindings: T(n) = T(n/2k) + kc • So, let: n/2k = 1 => n = 2k => k = log2n = lg n • Substituting back in (getting rid of k): T(n) = T(1) + c lg(n) = c lg(n) + c0 = O( lg(n) ) Solving the Fibonacci Recurrence • Lets go back to the Fibonnacci series • This is a linear homogenous recurrence with constant coefficients: fn - fn-1 - fn-2 = 0 • The characteristic equation is: x2 - x - 1= 0 MergeSort MergeSort Analysis T(n) = number of comparisons to mergesort an input of size n Mergesort recurrence Solving the mergesort recurrence = O(n Log (n) ) Quicksort

DOCUMENT INFO

Shared By:

Categories:

Tags:
Recursive Algorithms, Recursive Relations, Backward Substitution, Linear Search, Binary Search, Fibonacci Recurrence, Merge Sort, Merge Sort Analysis, Merge Sort Recurrence, Quick Sort

Stats:

views: | 22 |

posted: | 10/5/2011 |

language: | English |

pages: | 19 |

Description:
Recursive Algorithms with Examples: Recursive Relations and Algorithms Backword Subsititution with Linear, Binary search, Fibonacci Recurrence Relation and Merge Sort Analysis with Merge Sort Recurrence Relation and Quick Sort with Analysis with Examples...

OTHER DOCS BY abidnaeem466

Docstoc is the premier online destination to start and grow small businesses. It hosts the best quality and widest selection of professional documents (over 20 million) and resources including expert videos, articles and productivity tools to make every small business better.

Search or Browse for any specific document or resource you need for your business. Or explore our curated resources for Starting a Business, Growing a Business or for Professional Development.

Feel free to Contact Us with any questions you might have.